2018
DOI: 10.7589/2017-02-023
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Intensity of the Sinus Roundworm (Skrjabingylus Chitwoodorum) in Rabies-Negative Skunks of Texas, Usa

Abstract: :  Estimates of the distribution and prevalence of the sinus roundworm ( Skrjabingylus chitwoodorum) have been based largely on the inspection of skunk (Mephitidae) skulls showing damage from infections. We examined 595 striped skunks ( Mephitis mephitis) and nine hog-nosed skunks ( Conepatus leuconotus) that had tested negative for rabies by the Texas Department of State Health Services (US) between November 2010 and April 2015 to determine species of Skrjabingylus, prevalence and intensity of infection, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…A total of 19 Skrjabingylus samples that were reported in Hughes et al (2018) were used for the present study. Only samples that were preserved in ethanol or were frozen in the Angelo State Natural History Collections (ASNHC) were requested for our DNA analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 19 Skrjabingylus samples that were reported in Hughes et al (2018) were used for the present study. Only samples that were preserved in ethanol or were frozen in the Angelo State Natural History Collections (ASNHC) were requested for our DNA analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Skrjabingylus chitwoodorum has shown a high prevalence in Texas within the host species, M. mephitis. Hughes et al (2018) examined 595 striped skunks from Texas and extracted nematodes directly from the sinuses of 48.7% of them. The authors concluded that S. chitwoodorum had a bias for the left sinus and also that ecoregion and precipitation was not a determining factor of prevalence.…”
mentioning
confidence: 99%
“…Given that Skrjabingylus spp. can cause significant osteologic damage to the cranium, it is possible that this parasite could have significant impacts on individual fitness and population dynamics (Hughes et al, 2018; Lankester & Anderson, 1971).…”
Section: Discussionmentioning
confidence: 99%
“…Given that Skrjabingylus spp. can cause significant osteologic damage to the cranium, it is possible that this parasite could have significant impacts on individual fitness and population dynamics (Hughes et al 2018; Lankester and Anderson 1971).…”
Section: Discussionmentioning
confidence: 99%